Bertolt Brecht - Mumford, Meg (Routledge : London, 2009)
A life of flux -- Brecht's key theories -- The caucasian chalk circle : a model production -- Practical exercises and workshop
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Brecht, Bertolt